PERANAN MATAKULIAH PENDIDIKAN JASMANI DI PERGURUAN TINGGI - Sukadiyanto, Sukadiyanto (Jurnal Cakrawala Pendidikan, 2010)
Abstract Higher education students’ world reflects a life emphasizing academic morals. Unfortunately, there have been a lot of student fights triggered by trivial matters. This indicates a crisis in academic morals and stains campuses as centers for academic life. If students as the intellectual young generation were continuously involved the culture of fight, the nation would be in danger. Therefore, it is necessary to find a solution that can make use of students’ excessive energy to develop their creative potentials and imaginations through academic activities to make them mature and skillful. It is the responsibility of a higher education institution to develop students’ potentials so that they can give positive contributions to society through their activities. The Yogyakarta State University has made a breakthrough by including Physical Education (PE) in the 2009 Curriculum. It is an initial step to equip students with both hard skills and soft skills. PE makes use of physical activities in an attempt to attain educational goals. PE provides students with essential values that they can utilize in their campus and social life. In this way, students will possess mental toughness necessary to live the competitive life at present. Keywords: Physical Education, essential values